Measuring the Impact of COVID-19 on Young Adult Functional Capacity: A Comparative Study of Walking and Step Endurance Tests - Amput, Patchareeya; Srithawong, Arunrat; Maharan, Sinthuporn; Poncumhak, Puttipong; Phrompao, Patcharin; Wongsaya, Eakarach; Promsrisuk, Tichanon; Aueyingsak, Sahachat (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to evaluate and compare the functional capacity of young adults recovering from COVID-19 using the 6-Minute Walk Test (6MWT) and 2-Minute Step Test (2MST), focusing on cardiovascular parameters, and to examine correlations between these tests, demographic factors, and muscle strength. Materials and methods. A cross-sectional study was conducted with 34 young participants (mean age: 20.62 years, 88.24 % female), all experiencing mild post-COVID-19 symptoms. Muscle strength (grip and quadriceps strength) was assessed, and functional capacity was evaluated using the 6MWT and 2MST, with the test order randomized by drawing lots. Hemodynamic responses, fatigue, and dyspnea were measured before and after both tests. Paired t-tests were used to compare cardiovascular parameters and leg fatigue between the 6MWT and 2MST. Pearson’s correlation coefficient assessed relationships between both tests, demographics, and muscle strength. Results. The study revealed an increase in heart rate and leg fatigue after the 6MWT compared to the 2MST, whereas systolic blood pressure was elevated following the 2MST compared to the 6MWT. The 6MWT showed a significant positive correlation with the 2MST (r = 0.350, p = 0.043). Additionally, quadriceps strength was positively correlated with both the 6MWT (r = 0.372, p = 0.030) and the 2MST (r = 0.395, p = 0.021). Conclusions. The findings of this study indicate that both the 6MWT and 2MST are effective in assessing functional capacity in young individuals recovering from COVID-19, showing distinct physiological responses. Furthermore, quadriceps strength is correlated with both tests, highlighting the importance of muscle strength in recovery.